Pengaruh Latihan Menggunakan Metode Halangan dan Target Terhadap Pointing Olahraga Petanque pada Usia 10-12 Tahun - Al Bhaikhaqy, Dimas Risanggih; Prayoga, Aba Sandi; Bayu Utomo, Andy Widhiya (Universitas Hamzanwadi, 2022)
This study aims to determine the effect of training using the obstacle and target method on the accuracy of pointing in petanque sports. The problem in this study is the lack or weakness of accuracy in doing the pointing technique. This type of research is experimental-based quantitative. The population of this study were club petanque players, totaling 23 people. The sampling technique used was a saturated sample of 15 consisting of a target class, an obstacle class, and a control class. Data collection by pretest using obstacles and targets. After that, the pointing throw treatment was given 13 times in the target class, the obstacle class, and the control class carried out the pointing throw and after that the posttest was carried out. The results of the data and research hypothesis testing using a t-test (paired sample t-test) at a significance level of less than <0.05. From the research, the following results were obtained: 1) The target class based on the paired t test results obtained a sig of .000 This value is smaller than 0.05, so using the target training method can affect the accuracy of the pointing technique. 2) Obstacle class based on the paired t test results obtained a sig of .144. This value is greater than 0.05, so using the obstacle training method has no effect on the pointing technique. 3) The control class based on the results of the paired t-test, obtained sig 0.043. This value is smaller than 0.05, so it can be said that if you do not use the obstacle and target method, it can be concluded that the obstacle and target training method has an effect on the accuracy of pointing accuracy.